Density functional theory of doped superfluid liquid helium and nanodroplets. Issue 4 (2nd October 2017) - Ancilotto, Francesco; Barranco, Manuel; Coppens, François; Eloranta, Jussi; Halberstadt, Nadine; Hernando, Alberto; Mateo, David; Pi, Martí
Abstract: During the last decade, density function theory (DFT) in its static and dynamic time dependent forms, has emerged as a powerful tool to describe the structure and dynamics of doped liquid helium and droplets. In this review, we summarise the activity carried out in this field within the DFT framework since the publication of the previous review article on this subject [M. Barranco et al., J. Low Temp. Phys.142, 1 (2006)]. Furthermore, a comprehensive presentation of the actual implementations of helium DFT is given, which have not been discussed in the individual articles or are scattered in the existing literature.